MRI Evaluation of Axonal Remodeling After Combination Treatment With Xiaoshuan Enteric-Coated Capsule and Enriched Environment in Rats After Ischemic Stroke - Li, Man-Zhong; Zhan, Yu; Yang, Le; Feng, Xue-Feng; Zou, Hai-Yan; Lei, Jian-Feng; Zhao, Ting; Wang, Lei; Zhao, Hui (Frontiers in Physiology, 2019)
Xiaoshuan enteric-coated capsule (XSEC) is a compound Chinese medicine widely used for the treatment of ischemic stroke. Enriched environment (EE) is a rehabilitative intervention designed to facilitate physical, cognitive, and social activity after brain injury. This study aimed to assess whether the XSEC and EE combination could provide synergistic efficacy in axonal remodeling compared to that with a single treatment after ischemic stroke using magnetic resonance imaging (MRI) followed by histological analysis. Rats were subjected to permanent middle cerebral artery occlusion and treated with XSEC and EE alone or in combination for 30 days. T2-weighted imaging and diffusion tensor imaging (DTI) were performed to examine the infarct volume and axonal remodeling, respectively. The co-localization of Ki67 with NG2 or CNPase was examined by immunofluorescence staining to assess oligodendrogenesis. The expressions of growth associated protein-43 (GAP-43) and growth inhibitors NogoA/Nogo receptor (NgR)/RhoA/Rho-associated kinase2 (ROCK2) were measured using western blot and qRT-PCR. The Morris water maze (MWM) was performed to evaluate the cognitive function. MRI and histological measurements indicated XSEC and EE individually benefited axonal reorganization after stroke. Notably, XSEC + EE decreased infarct volume compared with XSEC or EE monotherapy and increased ipsilateral residual volume compared with vehicle group. DTI showed XSEC + EE robustly increased fractional anisotropy while decreased axial diffusivity and radial diffusivity in the injured cortex, striatum, and external capsule. Meanwhile, diffusion tensor tractography revealed XSEC + EE elevated fiber density in the cortex and external capsule and increased fiber length in the striatum and external capsule compared with the monotherapies. These MRI measurements, confirmed by histology, showed that XSEC + EE promoted axonal restoration. Additionally, XSEC + EE amplified oligodendrogenesis, decreased the expressions of NogoA/NgR/RhoA/ROCK2, and increased the expression of GAP-43 in the peri-infarct tissues. In parallel to these findings, rats treated with XSEC + EE exhibited higher cognitive recovery than those treated with XSEC or EE monotherapy, as evidenced by MWM test. Taken together, our data implicated that XSEC + EE exerted synergistic effects on alleviating atrophy and encouraging axonal reorganization partially by promoting oligodendrogenesis and overcoming intrinsic growth-inhibitory signaling, thereby facilitating higher cognitive recovery.